CO2 capture using ionic liquid hybrid sorbent: physical and chemical adsorption-desorption study - Tengku Azmi, Tengku Sharifah Marliza; Lahuri, Azizul Hakim; Taufiq-Yap, Yun Hin (Elsevier, 2022)
A hybrid sorbent of ionic liquid immobilized silica could enhance the adsorption capacity of CO2 capture compared to ionic liquid itself. This study emphasizes the physical and chemical adsorption-desorption study using 1-butil-3-methylimidazolium trifluoromethanesulfonate immobilized on silica, [bmim][CF3SO3]/SiO2. Different loading (1–10% mol/mol) of [bmim][CF3SO3] on silica were synthesized using sol-gel method. This work shows the most efficient adsorbent of 1%[bmim][CF3SO3]/SiO2 exhibits an adsorption capacity of 73.88 mg CO2/g. CO2 capture is dependent on the physical and chemical properties of the [bmim][CF3SO3]/SiO2 hybrid sorbent system. The studied shows the physical adsorption of CO2 is controlled by the porous nature of the sorbent. The formation of micro-partial pores on 1%[bmim][CF3SO3]/SiO2 is a major factor that contribute the higher physical adsorption capacity of CO2. Meanwhile, chemical properties i.e the base strength of the sorbent was found to affect the chemical adsorption-desorption of CO2. The presence of anions which consist of fluroalkyl functional group enhanced the capacity adsorption of CO2. There is a mixture between CO2 and CO was found during the chemical desorption process which indicates the occurrence of CO2 released and decomposition of [bmim][CF3SO3] at medium range temperature of 450–500 °C due to the Boudouard reaction. The sorbents used in this work were characterized using BET method, FTIR, and FESEM.